Designing Effective Learning Systems for Management Education: Student Roles, Requisite Variety, and Practicing What We Teach - Lengnick‐Hall, Cynthia A.; Sanders, Martha M. (Academy of Management Journal, 1997)
Process design principles from organization science offer insights for constructing learning systems that produce consistent, high-quality management education. We incorporated key process design concepts into a structure for graduate and undergraduate management and organizational behavior courses and then tested predictions using path analysis and comparative measures of dispersion. Results indicate that variety designed into a learning system can overcome extensive individual differences in student inputs and yield uniformly high levels of perceived personal effectiveness, organizational effectiveness, ability to apply course materials, and satisfaction with both course results and the educational process.